Health systems and health inequalities in Latin America - Antonella Bancalari; Samuel G. Berlinski; Giancarlo Buitrago; María Fernanda García; Dolores de la Mata; Marcos Vera-Hernández (Inter-American Development Bank (IDB), 2023)
The present paper outlines measures of disparity in healthcare access and health outcomes, drawing from the standardized metrics introduced in one related study (Bancalari et al., 2023). Beveridge countries seem to be less unequal than Bismarckian countries. Yet, there is no strong pattern in inequalities across our taxonomy, indicating certain unobserved variables of the health system might wield more influence over health and health care disparities than the overarching features defining our health system taxonomy. Finally, it will be analyzed how differences in healthcare use and health outcomes within countries are related to whether individuals benefit from either the contributory or the non-contributory subsystems and assess main factors explaining such differences by means of Oaxaca decompositions.
Keywords: I13; I14; I15; 330; Health Insurance; Public and Private; Health and Inequality; Health and Economic Development